THE USE OF CANVA-BASED ILLUSTRATED LEARNING MEDIA IN CULTURAL ARTS EDUCATION (SBDP) TO ENHANCE LEARNING INTEREST AMONG ELEMENTARY SCHOOL STUDENTS - Elansari; Sri Jamilah; Ikhsan Maulana (Universitas Islam Negeri Mataram, 2026)
This study investigates the use of the Canva application as illustrated learning media in Cultural Arts and Crafts (SBdP) instruction to enhance fifth-grade students’ interest in learning at MIS Sambinae, Bima City. Learning interest is a critical factor influencing students’ engagement and achievement, particularly in creative, visually oriented subjects such as the cultural arts. Thus, integrating digital learning media offers an effective strategy for fostering more engaging and meaningful learning experiences. This research adopts a qualitative descriptive approach, with data collected via classroom observations, interviews with the classroom teacher and school principal, and documentation of learning activities and instructional materials. The findings reveal that: (1) Canva-based illustrated media create a more interactive and visually appealing learning environment, boosting students’ attention and participation; and (2) incorporating visual media in SBdP stimulates students’ creativity, motivation, and confidence in producing artistic works. In conclusion, using the Canva application as a visual learning media significantly enhances students’ interest in learning, supports innovative arts education practices, and advances the integration of digital media in elementary cultural arts pedagogy.